The Cross-Section of Realized Stock Returns: The Pre-Compustat Evidence. - Davis, James L (Journal of Finance, 1994)
Using a database that is free of survivorship bias, this article finds that book-to-market equity, earnings yield, and cash flow yield have significant explanatory power with respect to the cross-section of realized stock returns during the period from July 1940 through June 1963. There is a strong January seasonal in the explanatory power of these variables, even though small stocks are, by construction, excluded from the sample.